Predictive value of Th17/Treg immune imbalance for disease severity and poor prognosis in children with respiratory syncytial virus pneumonia - Zhu, Minjuan; Liu, Jian (Frontiers in Pediatrics, 2025)
ObjectiveRespiratory syncytial virus pneumonia (RSVP) remains a major cause of pediatric hospitalization. This study evaluates the value of Th17/Treg imbalance in assessing disease severity and predicting prognosis among RSVP children.MethodsRSVP children (422 cases) during May 2022–May 2024 were retrospectively enrolled and divided into mild and moderate-to-severe groups based on disease severity. Additionally, 358 healthy children were recruited (the control group). Peripheral blood Th17 and Treg cell proportions were quantified by flow cytometry, with the Th17/Treg ratio calculated. Serum IL-17, IL-6, IL-10, and TGF-β1 levels were measured using ELISA. Logistic regression models were established to identify risk factors for poor prognosis. ROC curves were plotted to evaluate predictive performance.ResultsRSVP children demonstrated higher Th17 cell proportion, IL-17 and IL-6 levels, and Th17/Treg ratio than controls, alongside lower Treg cell proportion and IL-10 and TGF-β1 levels (all P < 0.001). These alterations correlated with disease severity and prognosis. Th17/Treg ratio and IL-17 were independent risk factors for poor prognosis, while IL-10 was a protective factor (all P < 0.05). The Th17/Treg ratio yielded an AUC of 0.831 (77.05% sensitivity, 77.01% specificity) for predicting poor prognosis. AUCs were 0.770 for IL-17 (67.21% sensitivity, 78.67% specificity) and 0.756 for IL-10 (57.38% sensitivity, 83.38% specificity). The combined model (Th17/Treg ratio + IL-17 + IL-10) achieved a superior AUC of 0.919 (93.44% sensitivity, 75.35% specificity; all P < 0.001).ConclusionPeripheral blood Th17/Treg imbalance is a characteristic of RSVP children. The combined detection of Th17/Treg ratio, IL-17, and IL-10 can help predict poor prognosis in affected children.